Outdoor program administration : principles and practices - Association of Outdoor Recreation and Education; Harrison, Geoff, 1970-; Erpelding, Mat, 1975- (Champaign, IL : Human Kinetics, 2012)
Outdoor recreation programming is a growing and diverse field that requires administrators to be ready to work in complex and multidisciplinary environments. Outdoor Program Administration: Principles and Practices will help both seasoned and new administrators—as well as students and emerging professionals—flourish in various settings, including university, military, government, commercial, and nonprofit organizations. You'll learn the best contemporary administrative strategies and practices from veteran professionals from the Association of Outdoor Recreation and Education (AORE). The AORE authors provide extensive coverage of all aspects of administrative duties and responsibilities from a diverse organizational setting. Outdoor Program Administration: Principles and Practices guides you in developing and sustaining programs in outdoor recreation settings across public, private, and nonprofit sectors. You will reap the benefits of the experience shared by the AORE authors, who also provide questions and critical thinking exercises that will enhance the materials and deepen your understanding. This reference explores all the issues pertinent to being a successful outdoor program administrator. The book has four sections: Outdoor Program Foundations, Program Design and Implementation, Staffing Considerations, and Facilities and Programs. Topics you'll delve into include •designing and developing programs; •risk management and legal considerations; •budgeting and financial operations; •marketing and land access (permits); •environmental stewardship; •staff recruitment, supervision, training, and assessment; and •management of indoor climbing walls and challenge courses.
Includes bibliographical references (p. 377-388) and index.
Keywords: Buitenactiviteiten; Management; Outdoor recreation -- Management; Outdoor recreation -- Planning; Planning